Determinants of Employee Work Satisfaction - Idris, Idris; Zuhri, Saefudin; Efendi, Mohammad (International Review of Management and Marketing, 2018)
Research has been conducted to examine the effect of work motivation, work environment and incentives on employee job satisfaction at the Jakarta Primary Tax Service Office. The population taken for this study were all employees of the Jakarta Primary Tax Service Office, amounting to 78 employees. Of the population of 1178 employees, 300 respondents will be taken for the instrument test and 48 respondents as the research sample. Data analysis using SPSS version 17.0 for Windows shows that: (1) There is a positive and significant influence of work motivation on employee job satisfaction at the Jakarta Primary Tax Service Office, (2) There is a positive and significant influence on the work environment on job satisfaction of Service Officers Tax Jakarta, (3) There is a positive and significant effect of incentives on employee job satisfaction at the Jakarta Primary Tax Service Office, (4) There is a positive and significant influence on work motivation, work environment and incentives together on employee job satisfaction Jakarta Primary Tax Service Office. Keywords: Work Motivation, Work Environment, Incentives and Employee Job Satisfaction. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7187